Liraglutide for patients with non-alcoholic steatohepatitis. - Dale, A; Hartley, P; Heneghan, C (Elsevier, 2016)
The Article by Matthew Armstrong and colleagues (Feb 13, p 679) reports different outcomes to those initially registered in the trial protocol.